Implikasi Pembelajaran Tutorial Bahasa Arab Terhadap Peningkatan Kemampuan Siswa - Nasihin, Khoirun; Jamalin, Fakron; Ningsih, Febri Yunita (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2024)
Arabic language learning tutorial at the MAN 2 Mataram Religious Program is an Arabic language learning enrichment program outside formal morning hours intended for religious program students who live in the dormitory. This research is a case study with qualitative research methods. The aim of this research is to 1) describe Arabic language tutorial learning in the MAN 2 Mataram religious program from the planning, implementation and evaluation stages, 2) Describe the implications of Arabic language tutorial learning on students' Arabic language abilities religious program at MAN 2 Mataram. Data was obtained through observation, interviews and documentation techniques. Then the data was analyzed using the interactive technique of the Miles, Huberman, and Saldana model with three stages: data condensation, data presentation and conclusion drawing. Then the data is tested for validity through triangulation of sources and techniques. From the research results, it is known that the main focus of Arabic language tutorial learning in the MAN 2 Mataram religious program is the emphasis on students' reading skills, while still paying attention to other language skills. The Arabic language learning tutorial program has been proven to make religious program students superior in the field of Arabic compared to students in other majors, both from cognitive, psychomotor and affective aspects.